GREEN MUSTARD FARMING PERFORMANCE IN CARINGIN KULON VILLAGE, CARINGIN DISTRICT, SUKABUMI REGENCY - M. Aditya Putra Risandi; Amalia Nur Milla; Ashrul Tsani (Universitas Muhammadiyah Makassar, 2026)
Green mustard farming is one of the horticultural agricultural activities that plays an important role in supporting farmers' income, especially in Caringin Kulon Village, Caringin District, Sukabumi Regency. This study aims to describe the performance of green mustard farming and analyze the economic feasibility of this farming. The study was conducted in December 2025 using a quantitative descriptive method. The data used consisted of primary data obtained through direct interviews using questionnaires to 30 green mustard farmers selected by purposive sampling, as well as secondary data from related agencies and supporting literature. Data analysis included analysis of farming performance, production costs, revenue, income, and business feasibility using the Revenue Cost Ratio (R/C Ratio). The results showed that the average area of ​​​​farmers' cultivated land was 0.13 ha with a farming management system that was still simple and dominated by hereditary experience. The total production cost of green mustard farming per planting season is Rp 1,546,612, with revenue of Rp 3,543,369 and net income of Rp 1,996,757. The R/C Ratio of 2.29 indicates that green mustard farming is economically viable and profitable for farmers. However, farmers still face obstacles in the form of price fluctuations and weak bargaining power in marketing. Overall, green mustard farming in Caringin Kulon Village has the potential to be developed as a source of income for farmers.